Integrating Classical and Contemporary Views on Asbab al-Nuzul: Implications for Qur'anic Interpretation and Social Issues - Ilahi, Ardelia Nihlah; Sanuri, S; Zainuddin, Muhammad Zendy (QiST: Journal of Quran and Tafseer Studies, 2025)
Previous studies on asbāb al-nuzūl primarily focus on hermeneutical approaches, legal derivation, and classical or contemporary exegetical perspectives. However, a significant research gap remains, as these studies rarely connect the occasions of revelation to modern socio-political challenges such as misinformation, negative media exposure, and their psychological impact on society. This study seeks to address this gap by integrating classical and contemporary frameworks of asbāb al-nuzūl with current societal issues. The objective of this research is to explain the methods used to determine authentic asbāb al-nuzūl, to examine the conceptual understanding of classical and modern scholars, to explore the functions of asbāb al-nuzūl, and to analyze its implications for Islamic legal rulings (fiqh) and contemporary social concerns. Using a qualitative library-based method, this study examines Qur'anic verses alongside authoritative classical and modern texts. Data were analyzed inductively through classification of methodological approaches, comparison of scholarly perspectives, and exploration of legal and social implications supported by relevant textual evidence. The findings show four major methods for determining asbāb al-nuzūl: selecting the most authentic narration, preferring the stronger (rājiḥ) narration, reconciling complementary reports, and acknowledging double revelation when reports cannot be combined. Classical scholars emphasize the indispensability of asbāb al-nuzūl for accurate interpretation, while contemporary scholars highlight its role in contextualizing Qur'anic teachings for modern realities. The implications of this study affirm that asbāb al-nuzūl is crucial for deriving legal rulings—such as the phased prohibition of alcohol and the legal reasoning behind ẓihār—and for strengthening the relevance of Qur'anic interpretation in addressing modern issues like misinformation, ethical criticism, and responsible public discourse. This demonstrates that the Qur'an's contextual wisdom remains essential for guiding contemporary society.